Policy on Principal Recruitment in Implementing Change Management the Education Office Jambi Province - Septariani Septariani; Mukhtar Mukhtar; Wahyudi Wahyudi (Universitas Muhammadiyah Enrekang, 2024)
This study investigates the recruitment policy of school principals in implementing change management at the Education Office Jambi Province. The research highlights how competency-based recruitment practices contribute to leadership effectiveness in driving educational reform. Using a qualitative case study approach, the study identifies critical components, such as the selection process, principal competencies, and challenges in implementation, including resistance to change and resource limitations. Findings emphasize the importance of comprehensive recruitment policies that align with both national standards and local educational needs. This research contributes to developing strategic frameworks for principal recruitment and offers actionable recommendations for policymakers to enhance educational leadership.